Fully Flexible Parallel Merge Sort for Multicore Architectures. (2nd December 2018) - Marszałek, Zbigniew; Woźniak, Marcin; Połap, Dawid
Abstract : The development in multicore architectures gives a new line of processors that can flexibly distribute tasks between their logical cores. These need flexible models of efficient algorithms, both fast and stable. A new line of efficient sorting algorithms can support these systems to efficiently use all available resources. Processes and calculations shall be flexibly distributed between cores to make the performance as high as possible. In this article we present a fully flexible sorting method designed for parallel processing. The idea we describe in this article is based on modified merge sort, which in parallel form is designed for multicore architectures. The novelty of this idea is in particular way of processing. We have developed a fully flexible method that can be implemented for a number of processors. The tasks are flexibly distributed between logical cores to increase the efficiency of sorting. The method preserves separation of concerns; therefore, each of the processors works separately without any cross actions and interruptions. The proposed method was described in theoretical way, examined in tests, and compared to other methods. The results confirm high efficiency and show that with each newly added processor sorting becomes faster and more efficient.